2005
DOI: 10.1203/01.pdr.0000157676.45088.8c
|View full text |Cite
|
Sign up to set email alerts
|

Use of Opioids in Asphyxiated Term Neonates: Effects on Neuroimaging and Clinical Outcome

Abstract: Perinatal asphyxia is a common cause of neurologic morbidity in neonates who are born at term. Asphyxiated neonates are frequently treated with analgesic medications, including opioids, for pain and discomfort associated with their care. On the basis of previous laboratory studies suggesting that opioids may have neuroprotective effects, we conducted a retrospective review of medical records of 52 neonates who were admitted to our neonatal intensive care unit between 1995 and 2002 and had undergone magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…Although this study has limitation, after adjustment for gestational age and propensity, prolonged sedation was not associated with poor neurologic outcomes at 5 y. In term infants suffering from hypoxic-ischemic encephalopathy, a retrospective study reported that postnatal morphine use was associated with improved outcomes, based on psychological assessments and neuroimaging studies (108). In the light of these findings, further data analyses of clinical trials examining the use of hypothermia should also investigate the effects of concomitant sedative or analgesic therapy on long-term neurodevelopmental outcomes (109 -111).…”
Section: Existing Human Data On Neurotoxicity Of Sedative Drugs Used mentioning
confidence: 70%
“…Although this study has limitation, after adjustment for gestational age and propensity, prolonged sedation was not associated with poor neurologic outcomes at 5 y. In term infants suffering from hypoxic-ischemic encephalopathy, a retrospective study reported that postnatal morphine use was associated with improved outcomes, based on psychological assessments and neuroimaging studies (108). In the light of these findings, further data analyses of clinical trials examining the use of hypothermia should also investigate the effects of concomitant sedative or analgesic therapy on long-term neurodevelopmental outcomes (109 -111).…”
Section: Existing Human Data On Neurotoxicity Of Sedative Drugs Used mentioning
confidence: 70%
“…Opioids have neuroprotective properties, 18,19 demonstrate increased levels in mammals during the natural process of hibernation, 20 and might have a more-pronounced effect during hypothermia by blunting the stress 10 and the metabolic and hormonal responses to hypothermia. 10,21 In addition, morphine levels are increased during hypothermia because of altered pharmacokinetic characteristics and decreased elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Taddio et al 26 demonstrated that intravenous morphine was more effective than topical tetracaine for the management of pain associated with central line placement in neonates. Angeles et al 45 showed that opioid use in asphyxiated term neonates had a positive effect on the neuroimaging outcomes and clinical outcomes at 18 months.…”
Section: Morphinementioning
confidence: 99%